Infective Endocarditis by Biofilm-Producing Methicillin-Resistant Staphylococcus aureus—Pathogenesis, Diagnosis, and Management - Ashlesha Kaushik; Helen Kest; Mangla Sood; Corey Thieman; Bryan W. Steussy; Michael Padomek; Sandeep Gupta (Antibiotics)
Infective endocarditis (IE) is a life-threatening condition with increasing global incidence, primarily caused by Staphylococcus aureus, especially methicillin-resistant strains (MRSA). Biofilm formation by S. aureus is a critical factor in pathogenesis, contributing to antimicrobial resistance and complicating the treatment of infections involving prosthetic valves and cardiovascular devices. Biofilms provide a protective matrix for MRSA, shielding it from antibiotics and host immune defenses, leading to persistent infections and increased complications, particularly in cases involving prosthetic materials. Clinical manifestations range from acute to chronic presentations, with complications such as heart failure, embolic events, and neurological deficits. Diagnosis relies on the Modified Duke Criteria, which have been updated to incorporate modern cardiovascular interventions and advanced imaging techniques, such as PET/CT (positron emission tomography, computed tomography), to improve the detection of biofilm-associated infections. Management of MRSA-associated IE requires prolonged antimicrobial therapy, often with vancomycin or daptomycin, needing a combination of antimicrobials in the setting of prosthetic materials and frequently necessitates surgical intervention to remove infected prosthetic material or repair damaged heart valves. Anticoagulation remains controversial, with novel therapies like dabigatran showing potential benefits in reducing thrombus formation. Despite progress in treatment, biofilm-associated resistance poses ongoing challenges. Emerging therapeutic strategies, including combination antimicrobial regimens, bacteriophage therapy, antimicrobial peptides (AMPs), quorum sensing inhibitors (QSIs), hyperbaric oxygen therapy, and nanoparticle-based drug delivery systems, offer promising approaches to overcoming biofilm-related resistance and improving patient outcomes. This review provides an overview of the pathogenesis, current management guidelines, and future directions for treating biofilm-related MRSA IE.